2022
DOI: 10.3390/app122211447
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Permeability of Microbial-Solidified Calcareous Sand Based on MICP

Abstract: In the construction of artificial islands in distant seas, calcareous sand has been widely used as a foundation filler due to its excellent mechanical properties and extensive availability in the marine environment. How to store more fresh water on the artificial islands by reducing its permeability is currently a great challenge. Microbial-induced carbonate precipitation (MICP) has always been considered as a great potential method to improve the cemented properties of calcareous sand, but the effect of grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Previous research on MICP-treated sands has consistently shown that the hydraulic conductivity decreases significantly as the cementation level increases even up to 10 orders of magnitude. This reduction in hydraulic conductivity was reported in several studies [51,76,79,[82][83][84][85][86][87][88]. However, there was an exception noted in the study by Whiffin et al [3], where the measured hydraulic conductivity showed little change after treatment.…”
Section: Hydraulic Conductivitysupporting
confidence: 65%
See 3 more Smart Citations
“…Previous research on MICP-treated sands has consistently shown that the hydraulic conductivity decreases significantly as the cementation level increases even up to 10 orders of magnitude. This reduction in hydraulic conductivity was reported in several studies [51,76,79,[82][83][84][85][86][87][88]. However, there was an exception noted in the study by Whiffin et al [3], where the measured hydraulic conductivity showed little change after treatment.…”
Section: Hydraulic Conductivitysupporting
confidence: 65%
“…This was confirmed by other studies in which the hydraulic conductivity of cemented sand was found to be influenced also by its grain gradation in a similar manner. The reduction in the hydraulic conductivity coefficient during each MICP treatment cycle increased with higher values of the uniformity coefficient (C u ) and the curvature coefficient (C c ) [86].…”
Section: Hydraulic Conductivitymentioning
confidence: 99%
See 2 more Smart Citations
“…5. Inhibitory effect of calcium and magnesium ions mixed pollutants on urease activity: a) when the proportion of calcium ions in mixed pollutants is 0.2, b) when the proportion of calcium ions in mixed pollutants is 0.5, c) when the proportion of calcium ions in mixed pollutants is 0.8. low the proportion of calcium ions) magnesium ions react with negatively charged functional groups on the surface of microorganisms [20,21], calcium ions react with carbon dioxide or carbonate ions in wastewater to form precipitates on the surface of microorganisms, which together inhibit the metabolic activities of microorganisms, and the interaction between the two ions is synergistic. When the concentration of calcium ions in mixed pollutants is increasing, more calcium carbonate crystals will be generated, while the existence of magnesium ions will hinder some calcium ions from precipitating, and the synergistic effect between the two ions will decrease.…”
Section: The Regularity Of Inhibitory Effect Of Calcium and Magnesium...mentioning
confidence: 99%